Preparation method for controllably synthesizing monodisperse poly (2, 6-diaminopyridine) mesoporous nanospheres through directed self-assembly of single micelles as well as product and application thereof
Through the single micelle directional self-assembly method, monodispersed poly2,6-diaminopyridine mesoporous nanospheres were prepared using block copolymers and 2,6-diaminopyridine and other raw materials, which solved the problem of using harmful etchants in the prior art, achieved low-cost and environmentally friendly material preparation, and showed excellent electrochemical properties.
Patent Information
- Application Number
- CN202411911770.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, when preparing mesoporous materials, harmful hydrofluoric acid is needed as template etchant, resulting in environmental pollution and high material preparation costs.
Monodispersed poly2,6-diaminopyridine mesoporous nanospheres were prepared by mediating water, ethanol and tetrahydrofuran using single micelle directional self-assembly and controlled synthesis.
The preparation of mesoporous nanospheres through green, simple and low-cost synthetic paths at room temperature is realized, which reduces the environmental pollution and cost of material preparation, and has high specific surface area and excellent electrochemical properties.
Smart Images

Figure CN119751961A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage material preparation, and specifically relates to a preparation method of single micelle directional self-assembly and controllable synthesis of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres, and its products and applications. Background Art
[0002] Porous organic polymers are a class of porous materials with high molecular design capabilities. Their skeletons are composed of organic molecules, with diverse chemical structures and rich functional properties. This type of material has attracted widespread attention for its high specific surface area, adjustable pore size distribution, and excellent chemical and thermal stability. The porous structure of porous organic polymers is mainly composed of organic monomers connected by covalent bonds. Through various synthetic strategies such as solution method and solid phase method, microporous, mesoporous or macroporous structures can be formed. These pores provide ideal channels for molecular adsorption and transport.
[0003] Poly(2,6-diaminopyridine) (PDAP) is a promising anode material for zinc-ion batteries due to its unique combination of properties. Its redox-active amino and pyridine groups enable efficient and reversible zinc-ion interactions, while the flexible organic framework accommodates ion insertion and extraction, ensuring excellent cycling stability. Compared with traditional inorganic materials, PDAP has a high theoretical capacity and is lightweight. Its material cost-effectiveness and environmental friendliness have significant advantages over metal-based electrodes, making it an ideal choice for portable electronics applications. In aqueous electrolytes, PDAP has stable chemical properties, which enables high reliability of performance in lithium-ion batteries; in addition, the nitrogen-rich functional groups in PDAP help improve the mobility of zinc ions, while its soft structure helps reduce the formation of dendrites, thereby improving safety and service life. With its scalable synthesis method and tunable properties, PDAP is well suited for a variety of energy storage applications from power grid systems to portable electronics.
[0004] Generally, the preparation of mesoporous materials by using silica nanoparticles as templates requires the use of hydrofluoric acid as an etchant for the template. Hydrofluoric acid is very harmful to the environment, and the solution after etching requires additional waste liquid treatment, which directly increases the cost of material preparation. Summary of the invention
[0005] In view of the defects of the prior art, the present invention aims to provide a method for preparing single micelle directional self-assembly and controllably synthesized monodisperse poly-2,6-diaminopyridine mesoporous nanospheres.
[0006] Another object of the present invention is to provide a single micelle directed self-assembly and controllably synthesized monodisperse poly-2,6-diaminopyridine mesoporous nanosphere product prepared by the above method.
[0007] Another object of the present invention is to provide an application of the above product.
[0008] The object of the present invention is achieved through the following scheme: a method for preparing monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by directional self-assembly of single micelles and controllable synthesis, using 2,6-diaminopyridine, ammonium persulfate, and block copolymer polyethylene oxide-polystyrene copolymer as raw materials, using water, ethanol, and tetrahydrofuran as self-assembly dispersants to adjust the particle size of poly-2,6-diaminopyridine spherical micelles, and preparing monodisperse poly-2,6-diaminopyridine mesoporous nanospheres, comprising the following steps: First, a block copolymer of polyethylene oxide-polystyrene with a relative molecular mass of 8000-25000 is dissolved in tetrahydrofuran, and then an ethanol / water mixed solution is added to the solution at a drop rate of 1-5 ml / min under uniform stirring, and a regulator is added at the same time; after sufficient stirring, a certain amount of 2,6-diaminopyridine is added to the mixed solution, and finally an ammonium persulfate aqueous solution is added, wherein the molar ratio of the 2,6-diaminopyridine to the ammonium persulfate is 1-3:1; the mixture is stirred at room temperature for 12-48 hours, centrifuged, and washed with tetrahydrofuran, water and ethanol respectively. The mixture is dried at 60°C for 12 hours to obtain a monodisperse poly-2,6-diaminopyridine mesoporous nanosphere powder.
[0009] The present invention provides a method for preparing single micelle directional self-assembly and controllable synthesis of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres. The block copolymer polyethylene oxide-polystyrene used in the method only needs to be dissolved using tetrahydrofuran to effectively remove the template. At the same time, the dissolved block copolymer template will not undergo chemical structure changes and can be recycled, making the material preparation cost lower and more environmentally friendly.
[0010] The regulator is one of deionized water, anhydrous ethanol, anhydrous methanol and petroleum ether.
[0011] The present invention provides a single micelle directed self-assembly and controllably synthesized monodisperse poly-2,6-diaminopyridine mesoporous nanosphere, which is prepared according to any of the above methods; the nanosphere composite material has a high specific surface area, contains nitrogen-doped carbon chains and a regular mesoporous structure for diffusion, and is used for the storage of zinc ions in the negative electrode of a zinc ion battery.
[0012] The present invention provides a single micelle directed self-assembly and controllably synthesized monodisperse poly-2,6-diaminopyridine mesoporous nanosphere for use as an electrode material in a new energy battery.
[0013] The electrochemical performance test of monodisperse poly 2,6-diaminopyridine mesoporous nanospheres was carried out as follows: 35 mg monodisperse poly 2,6-diaminopyridine mesoporous nanospheres, 10 mg acetylene black, 5 mg polyvinylidene fluoride PVDF and 0.1 ml N-methylpyrrolidone were weighed and fully mixed, the mixture was evenly coated on a conductive carbon cloth, the carbon cloth was assembled into a battery with a zinc sheet, a 0.1 mol / L zinc sulfate solution, a glass fiber separator and a battery shell, and then the electrochemical performance of the assembled battery was tested. The electrochemical test showed that the monodisperse poly 2,6-diaminopyridine mesoporous nanospheres had good electrochemical performance as an electrode material for aqueous zinc ion batteries.
[0014] The principle of the present invention is that, by adopting the above-mentioned preparation process, after the block copolymer polyethylene oxide-polystyrene is dissolved in tetrahydrofuran, when a mixed solution of water and ethanol is added, the block copolymer ethylene oxide-polystyrene will form spherical micelles, and the particle size of the spherical micelles can be adjusted by using a regulator such as water, and 2,6-diaminopyridine undergoes a polymerization reaction in an ammonium persulfate environment. During the polymerization reaction, the poly-2,6-diaminopyridine will wrap the spherical micelles to form a composite material of poly-2,6-diaminopyridine and the block copolymer. After the composite material is separated by centrifugation, the block copolymer ethylene oxide-polystyrene micelles are dissolved by tetrahydrofuran to finally form monodisperse poly-2,6-diaminopyridine mesoporous nanospheres.
[0015] The method of the present invention uses block copolymer polyethylene oxide-polystyrene, 2,6-diaminopyridine and ammonium persulfate as raw materials, and prepares monodisperse poly 2,6-diaminopyridine mesoporous nanospheres through a green, simple and low-cost room temperature synthesis route. The obtained composite material can be used for the storage of zinc ions in the negative electrode of zinc ion batteries and shows a high specific capacity. It has the characteristics of simple preparation method, low preparation cost, green and environmental protection, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 and Figure 2 This is a scanning electron microscope image of the monodisperse poly-2,6-diaminopyridine mesoporous nanospheres obtained in Example 1.
[0017] As can be seen from the figure, the material is composed of uniform mesoporous nanospheres. The diameter of the nanospheres is distributed in the range of 80~120nm, the pore size is distributed in the range of 25~30nm, and the mesopores are arranged in a certain ordered structure in the nanospheres. Figure 3 Electrochemical performance diagram of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres as electrode materials for aqueous zinc-ion batteries. DETAILED DESCRIPTION
[0018] This embodiment is implemented on the premise of the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0019] Example 1 The invention discloses a method for controlling the synthesis of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by directional self-assembly of single micelles. 2,6-diaminopyridine, ammonium persulfate and block copolymer polyethylene oxide-polystyrene copolymer are used as raw materials, water, ethanol and tetrahydrofuran are used as self-assembly dispersants to adjust the particle size of poly-2,6-diaminopyridine spherical micelles, and monodisperse poly-2,6-diaminopyridine mesoporous nanospheres are prepared. The preparation steps are as follows: Accurately weigh 50 mg of block copolymer polyethylene oxide-polystyrene with an average molecular weight of 15000, first dissolve the weighed block copolymer polyethylene oxide-polystyrene in 2 ml of tetrahydrofuran, and under uniform stirring, add 1 ml of water and 2 ml of ethanol / water mixed solution at a dropping rate of 2 ml / min to the solution, and add 3.5 ml of regulator water to obtain a mixed solution; after sufficient stirring, add 67.1 mg of 2,6-diaminopyridine to the mixed solution, and after the solid is completely dissolved, add 85.7 mg of ammonium persulfate; stir at room temperature for 12 hours, centrifuge, and wash thoroughly with tetrahydrofuran, water and ethanol respectively; dry at 60°C for 12 hours to obtain a monodisperse poly 2,6-diaminopyridine mesoporous nanosphere powder.
[0020] Figure 1 and Figure 2 This is a scanning electron microscope image of the poly 2,6-diaminopyridine mesoporous nanospheres obtained in Example 1. As can be seen from the figure, the material is composed of uniform mesoporous nanospheres, the diameter of the nanospheres is distributed in the range of 80-120 nm, the pore size is distributed in the range of 25-30 nm, and the mesopores are arranged in a certain orderly structure in the nanospheres.
[0021] The electrochemical performance test of monodisperse poly 2,6-diaminopyridine mesoporous nanospheres was carried out as follows: 35 mg of monodisperse poly 2,6-diaminopyridine mesoporous nanospheres, 10 mg of acetylene black, 5 mg of polyvinylidene fluoride PVDF and 0.1 ml of N-methylpyrrolidone were weighed and mixed thoroughly, and the mixture was evenly coated on a conductive carbon cloth, and the carbon cloth was assembled into a battery with a zinc sheet, a 0.1 mol / L zinc sulfate solution, a glass fiber separator and a battery shell, and then the electrochemical performance of the assembled battery was tested. The electrochemical test showed that monodisperse poly 2,6-diaminopyridine mesoporous nanospheres had good electrochemical performance as electrode materials for aqueous zinc ion batteries. Figure 3 shown.
[0022] Example 2 A method for the controlled synthesis of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by single micelle directional self-assembly is similar to Example 1 and is prepared according to the following steps: Accurately weigh 50 mg of a block copolymer polyethylene oxide-polystyrene with an average molecular weight of 15000, dissolve it in 2 ml of tetrahydrofuran, and under stirring, drop a mixed solution of 1 ml of water and 2 ml of ethanol at a dropping speed of 2 ml per minute, stir evenly, then add 5 ml of water, stir evenly and mix, then add 67.1 mg of 2,6-diaminopyridine, after the solid is completely dissolved, add an ammonium persulfate solution mixed with 85.7 mg of ammonium persulfate and 0.2 ml of water, stir at room temperature for 12 hours; centrifuge and separate, wash the product with tetrahydrofuran, water and ethanol for multiple times; dry at 60°C for 12 hours to obtain a monodisperse poly 2,6-diaminopyridine mesoporous nanosphere powder solid.
[0023] The electrochemical performance diagram shows that the electrode material prepared by this invention has higher electrochemical performance.
[0024] Example 3 A method for the controlled synthesis of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by single micelle directional self-assembly is similar to Example 1 and is prepared according to the following steps: Accurately weigh 50 mg of a block copolymer polyethylene oxide-polystyrene with an average molecular weight of 25000, dissolve it in 2 ml of tetrahydrofuran, and add a mixed solution of 1 ml of water and 2 ml of ethanol at a dropping speed of 2 ml per minute under stirring. After stirring evenly, add 3.5 ml of water and stir evenly, then add 67.1 mg of 2,6-diaminopyridine. After the solid is completely dissolved, add 85.7 mg of ammonium persulfate and 0.2 ml of water mixed with ammonium persulfate solution, and stir at room temperature for 12 hours; centrifuge and separate, wash the product with tetrahydrofuran, water and ethanol for multiple times; dry at 60°C for 12 hours to obtain a monodisperse poly 2,6-diaminopyridine mesoporous nanosphere powder solid.
[0025] The electrochemical performance diagram shows that the electrode material prepared by this invention has higher electrochemical performance.
[0026] Example 4 A method for the controlled synthesis of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by single micelle directional self-assembly is similar to Example 1 and is prepared according to the following steps: Accurately weigh 50 mg of block copolymer polyethylene oxide-polystyrene with an average molecular weight of 15000, dissolve it in 2 ml of tetrahydrofuran, and add a mixed solution of 1 ml of water and 2 ml of ethanol at a dropping speed of 2 ml per minute under stirring. After stirring evenly, add 10 ml of water, stir evenly, then add 67.1 mg of 2,6-diaminopyridine, and after the solid is completely dissolved, add 85.7 mg of ammonium persulfate and 0.2 ml of water mixed with ammonium persulfate solution, and stir at room temperature for 24 hours. Centrifuge and wash the product with tetrahydrofuran, water, and ethanol for many times; dry at 60°C for 12 hours to obtain a monodisperse poly 2,6-diaminopyridine mesoporous nanosphere powder solid.
[0027] The electrochemical performance diagram shows that the electrode material prepared by this invention has higher electrochemical performance.
[0028] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by directional self-assembly of single micelles and controllable synthesis, characterized in that: The method uses 2,6-diaminopyridine, ammonium persulfate and block copolymer polyethylene oxide-polystyrene copolymer as raw materials, uses water, ethanol and tetrahydrofuran as self-assembly dispersants to adjust the particle size of poly-2,6-diaminopyridine spherical micelles, and prepares monodisperse poly-2,6-diaminopyridine mesoporous nanoparticles, comprising the following steps: First, a block copolymer polyethylene oxide-polystyrene with a relative molecular mass of 8000-25000 is dissolved in tetrahydrofuran, and an ethanol / water mixed solution is added dropwise to the solution at a dropping rate of 1-5 ml / min after uniform stirring, and a regulator is added at the same time; after sufficient stirring, 2,6-diaminopyridine is added to the mixed solution, and finally an ammonium persulfate aqueous solution is added, wherein the molar ratio of the 2,6-diaminopyridine to the ammonium persulfate is (1-3):1; the mixture is stirred at room temperature for 12-48 hours, centrifuged, and washed with tetrahydrofuran, water and ethanol respectively; and dried at 60°C for 12 hours to obtain a monodisperse poly 2,6-diaminopyridine mesoporous nanosphere powder.
2. The method for preparing monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by directed self-assembly of single micelles and controllable synthesis according to claim 1, characterized in that: The regulator is one of deionized water, anhydrous ethanol, anhydrous methanol and petroleum ether.
3. The method for preparing monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by directed self-assembly of single micelles and controllable synthesis according to claim 1 or 2, characterized in that: Prepare as follows: Accurately weigh 50 mg of block copolymer polyethylene oxide-polystyrene with an average molecular weight of 15000, first dissolve the weighed block copolymer polyethylene oxide-polystyrene in 2 ml of tetrahydrofuran, and under uniform stirring, add 1 ml of water and 2 ml of ethanol / water mixed solution at a dropping rate of 2 ml / min to the solution, and add 3.5 ml of regulator water to obtain a mixed solution; after sufficient stirring, add 67.1 mg of 2,6-diaminopyridine to the mixed solution, and after the solid is completely dissolved, add 85.7 mg of ammonium persulfate; stir at room temperature for 12 hours, centrifuge, and wash thoroughly with tetrahydrofuran, water and ethanol respectively; dry at 60°C for 12 hours to obtain a monodisperse poly 2,6-diaminopyridine mesoporous nanosphere powder.
4. The method for preparing monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by directed self-assembly of single micelles and controllable synthesis according to claim 1 or 2, characterized in that: The preparation method is prepared according to the following steps: accurately weigh 50 mg of a block copolymer polyethylene oxide-polystyrene with an average molecular weight of 15,000, dissolve it in 2 ml of tetrahydrofuran, and add a mixed solution of 1 ml of water and 2 ml of ethanol at a dropping speed of 2 ml per minute while stirring. After stirring evenly, add 5 ml of water and stir evenly, then add 67.1 mg of 2,6-diaminopyridine, and after the solid is completely dissolved, add an ammonium persulfate solution mixed with 85.7 mg of ammonium persulfate and 0.2 ml of water, and stir at room temperature for 12 hours; centrifuge and separate, wash the product with tetrahydrofuran, water and ethanol for multiple times; dry at 60° C. for 12 hours to obtain a monodisperse poly 2,6-diaminopyridine mesoporous nanosphere powder solid.
5. The method for preparing monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by directed self-assembly of single micelles and controllable synthesis according to claim 1 or 2, characterized in that: The preparation method is prepared according to the following steps: accurately weigh 50 mg of a block copolymer polyethylene oxide-polystyrene with an average molecular weight of 25,000, dissolve it in 2 ml of tetrahydrofuran, and add a mixed solution of 1 ml of water and 2 ml of ethanol at a dropping speed of 2 ml per minute while stirring. After stirring evenly, add 3.5 ml of water and stir evenly, then add 67.1 mg of 2,6-diaminopyridine. After the solid is completely dissolved, add an ammonium persulfate solution mixed with 85.7 mg of ammonium persulfate and 0.2 ml of water, and stir at room temperature for 12 hours; centrifuge and separate, wash the product with tetrahydrofuran, water and ethanol for multiple times; dry at 60°C for 12 hours to obtain a monodisperse poly 2,6-diaminopyridine mesoporous nanosphere powder solid.
6. The method for preparing monodisperse poly-2,6-diaminopyridine mesoporous nanospheres by directed self-assembly of single micelles and controllable synthesis according to claim 1 or 2, characterized in that: The preparation is as follows: accurately weigh 50 mg of a block copolymer of polyethylene oxide-polystyrene with an average molecular weight of 15,000, dissolve it in 2 ml of tetrahydrofuran, add a mixed solution of 1 ml of water and 2 ml of ethanol at a dropping speed of 2 ml per minute under stirring, stir evenly, then add 10 ml of water, stir evenly, then add 67.1 mg of 2,6-diaminopyridine, after the solid is completely dissolved, add 85.7 mg of ammonium persulfate and 0.2 ml of water mixed with ammonium persulfate solution, stir at room temperature for 24 hours. Centrifuge, wash the product with tetrahydrofuran, water, and ethanol for many times; dry at 60°C for 12 hours to obtain a monodisperse poly 2,6-diaminopyridine mesoporous nanosphere powder solid.
7. A single micelle directed self-assembly and controllable synthesis of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres, characterized in that Prepared according to any one of claims 1-6; the composite material has a high specific surface area, contains nitrogen-doped carbon chains and a regular mesoporous structure for diffusion, and is used for storing zinc ions in the negative electrode of a zinc ion battery.
8. Use of the single micelle directed self-assembly and controllable synthesis of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres according to claim 6 as an electrode material in new energy batteries.
9. A battery prepared by the single micelle directed self-assembly and controllable synthesis of monodisperse poly-2,6-diaminopyridine mesoporous nanospheres according to claim 6, characterized in that the battery is assembled according to the following method: Weigh 35 mg of monodisperse poly 2,6-diaminopyridine mesoporous nanospheres, 10 mg of acetylene black, 5 mg of polyvinylidene fluoride PVDF and 0.1 ml of N-methylpyrrolidone and mix them thoroughly. The mixture is evenly coated on a conductive carbon cloth, and the carbon cloth is assembled into a battery with a zinc sheet, a 0.1 mol / L zinc sulfate solution, a glass fiber separator and a battery shell.